(untitled) (Journal of Lithic Studies, 2016)
In order to examine the hypothesis of our knowledge on the Vinča chipped stone industry which was spreading on the territory of Serbia during the Late Neolithic until the Chalcolithic (the end of the 6th and the beginning of the 5th millennia BCE) and the previously noticed changes within it, we started from the question about the process of chipped stone tool production and the life cycle of artefacts. A series of preparatory activities in making replicas of flint sickles and the realization of a harvesting process contributed to gaining better knowledge on sequences of stone production technology, from the supply strategy to the production and utilization of artefacts. The main goal of the experiment was to obtain authentic traces of use on the working edges and creation of the first visual comparative database with examples from the region. Preliminary results essentially influenced our determination of the methods applied for reduction sequences during the Vinča culture. A significant result was achieved with the first quantifications of raw materials for making tools, such as a sickle and needs during one season, as well as with the precise definition of areas of sown land necessary for maintenance of an average Vinča family.